Advances in the treatment of secondary and tertiary hyperparathyroidism - Li-Xi Zhang; Ben Zhang; Xu-Yao Liu; Zi-Ming Wang; Peng Qi; Tong-Yue Zhang; Qiang Zhang (Frontiers in Endocrinology, 2022)
Secondary hyperparathyroidism (SHPT) and tertiary hyperparathyroidism (THPT) are common and complicated clinical endocrine diseases. The parathyroid glands maintain endocrine homeostasis by secreting parathyroid hormone to regulate blood calcium levels. However, structural alterations to multiple organs and systems occur throughout the body due to hyperactivity disorder in SHPT and THPT. This not only decreases the patients’ quality of life, but also affects mortality. Since current treatments for these diseases remains unclear, we aimed to develop a comprehensive review of advances in the treatment of SHPT and THPT according to the latest relevant researches.